LRRC4 Deficiency Drives Premature Ovarian Insufficiency by Disrupting Metabolic Homeostasis in Granulosa Cells - Yujie Shang; Yunjun Li; Di Han; Kun Deng; Wei Gao; Minghua Wu (Advanced Science)
Abstract Premature ovarian insufficiency (POI), defined by early loss of ovarian activity before the age of 40 years, is the leading cause of infertility and systematic aging in women, posing a public health challenge worldwide. However, its molecular etiology and therapeutic options are still lacking. Here, leucine‐rich repeat containing 4 (LRRC4) is identified as a critical regulator of folliculogenesis expressed in granulosa cells (GCs), which contributes to ovarian reserve maintenance. LRRC4 deficiency triggers defective oocyte maturation and excessive follicular atresia through inhibition of GC differentiation and ultimately leads to POI. Mechanistically, LRRC4 balances mitochondrial fission and fusion to inhibit excessive mitophagy by promoting the K48‐linked ubiquitination degradation of Yes‐associated protein (YAP), thereby maintaining the metabolic homeostasis of mitochondrial aerobic respiration and glycolysis. Importantly, targeting LRRC4 normalized follicular development and ovarian function in POI model mice. In conclusion, these data reveal the novel pathogenesis of POI and suggest that LRRC4 is a potential target for the diagnosis and treatment of POI.